Influence Of Supplier Integration, Human And Technical Lean Practices On Operational Performance Of Semiconductor Industry: Knowledge Base Engineering As A Mediator And Technological Turbulence As A Moderator - Cheng, Chee Hooi (2023)
Semiconductor firm in developing countries face intense competition resulted occurrence of factory closure and relocation despite well established. Hence, this research was designed and developed to understand holistic lean manufacturing practices that breakdown into human lean practice, technical lean practice and supplier integration toward financial and non-financial operational performance metrics in Malaysia’s semiconductor industries. The contribution of the research objective enables future researchers to gain comprehension of various variables relevant to operational performance in developing countries. This research adds to the novelty with the introduction of knowledge base engineering and technological turbulence in the model allowing for a robust understanding of factors that can affect firm operational performance. This research was conducted with 149 valid responses from 237 firms in the semiconductor industry population of Malaysia, where the semiconductor industry is one of the industries with high technology dynamics, a short product life cycle, high expenditure, and yet high demand. The collected data were processed and analysed using SPSS and SmartPLS software.